IMPROVING STUDENTS’ ABILITY IN EXPRESSING OPINION THROUGH GROUP INVESTIGATION AT THE STUDENTS CLASS XI IPA 1 SEMESTER 1 SMA NEGERI 1 ABUNG SEMULI ACADEMIC YEAR 2016-2017 - A. Mukhtar Majid (Universitas Muhammadiyah Kotabumi, 2018)
The objective of this research is to make the teaching learning of English at class XI IPA 1 of SMA Negeri 1 Abung Semuli, academic year 2016-2017 become interesting and effective. The research is classroom action research conducted in two cycles that involves plan, action, observation and reflection. The subject of the research was class XI IPA 1 that consists of 37 students (25 females and 12 males ). There were four instruments used in the reseach : teacher’s activity, students’ activity, active students and learning achievement. This study found that the use of Group Investigation model of learning can increase the effectiveness the English learning process at class XI IPA 1. The effectiveness of learning process is shown by improvement of the achievement at (1) the percentage of teacher’s activity that reached the target from 61.95% (cycle 1) becomes 80% (cycle 2) or increased 18,05%.(2) The percentage of students’ activity in cycle 1 was 41,66 % became 65,91% that meant the increased 24,25 %,(3) the persentage of active students also increased from 40,54 % (cycle 1) to 83,78 % (cycle 2) , the increase was 43,24 %, and (4) the percentage of speaking score was 24,32% (cycle 1) became 73,00% (cycle 2), means the increase wa 48,68 %. The result of learning using Group Investigatio model is achieved through the following stages: (1) pre-activity, teacher prepared students by informing the learning objective, giving motivation, preparing the material and putting the students into groups. (2)main step, the students in group were distributed the topic problem, group presentation, personal task, plenary discussion, conclusion and (3) post-activity, making a resume of the materail and teaching learning reflection.